2016
DOI: 10.5539/ibr.v9n11p178
|View full text |Cite
|
Sign up to set email alerts
|

When Satisfaction with Work-family Balance Pays

Abstract: This study examines the mechanism through which family supportive environments in organizations (i.e. family supportive supervisor behaviors and work-family friendly culture) relate to turnover intentions. In a sample of 340 individuals, analysis using structural equation modeling showed that satisfaction with work-family balance mediates the relation between family supportive environments in organizations and turnover intentions. Thus, family supportive environments in organizations facilitate greater satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Regarding measurement, 21% of studies have used either the FSSB-LF version or an adapted version, 21% used either the FSSB-SF version or an adapted version, and 57% used an alternate measure. Furthermore, FSSB has become a construct of international interest with studies conducted in Europe (e.g., Beham et al, 2014;Koch & Binnewies, 2015), Asia (e.g., Aryee et al, 2013;Lv, 2016), South America (e.g., Kim et al, 2016;Las Heras et al, 2015), and Africa (e.g., Bosch et al, 2018), in addition to the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding measurement, 21% of studies have used either the FSSB-LF version or an adapted version, 21% used either the FSSB-SF version or an adapted version, and 57% used an alternate measure. Furthermore, FSSB has become a construct of international interest with studies conducted in Europe (e.g., Beham et al, 2014;Koch & Binnewies, 2015), Asia (e.g., Aryee et al, 2013;Lv, 2016), South America (e.g., Kim et al, 2016;Las Heras et al, 2015), and Africa (e.g., Bosch et al, 2018), in addition to the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the articles examining job satisfaction, four articles Opposite commitment, turnover intention outcomes have also been well researched, with nine articles demonstrating negative relationships with FSSB (e.g., Hammer et al, 2009;Hammer et al, 2013). Seven articles provide support for indirect relationships, with WTFC (Hill et al, 2016), perceptions of control (Thompson & Prottas, 2006), POS (Allen, 2001;Hill et al, 2016;Las Heras et al, 2015), satisfaction with work-family balance (Kim, Las Heras, & Escribano, 2016), and LMX (Bagger & Li, 2014) acting as mediators. Odle-Dusseau et al (2012) found that WTFE, but not WTFC, mediated the relationship between FSSB and turnover intentions.…”
Section: Job Attitude Outcomesmentioning
confidence: 99%